A Stepwise Multiple Regression Analysis of Factors Influencing the Decision to Choose Freight Companies' Services - Sukkrajang, Chananan; sukkrajang, kantamon; Rattanakool, Tanarat (Academic Journal of Industrial Technology Innovation, 2024)
A stepwise multiple regression analysis was conducted to examine the factors influencing consumers' decisions in choosing freight forwarding companies. The objectives were to investigate the relationships between marketing strategy factors and consumers' decisions in choosing freight forwarding companies in Songkhla province, Thailand; and to develop a predictive equation using stepwise multiple regression analysis. Data were collected from 404 consumers who used freight forwarding services in Songkhla province. Pearson's correlation coefficient was used to determine the relationship between marketing strategies and other factors influencing the decision to use freight forwarding services. Stepwise multiple regression analysis was employed to create a predictive equation. The study found that the overall level of marketing strategy in influencing the decision to use freight forwarding services was moderate ( = 3.345). The correlation coefficient analysis revealed a statistically significant positive relationship at the .01 level between marketing strategies and other factors influencing the decision to use freight forwarding companies. The location factor and the product service factor were identified as significant predictors of marketing strategy in the decision to use freight forwarding services.